Nutritional Status and Child Development in Phrae Province - Akepatcha, Kanjana; Pongpan, Sarinya; Sansiriwong, Sopawadee (Journal of Health Science of Thailand, 2018)
The objectives of this survey research, conducted during August - September 2006, were to study nutritional conditions, child development, and factors related to development of children aged 1-3 years. Samples were pairs of children and their parents selected by 2 -stage stratified random sampling. It was found that most of their parents had primary education, working as laborers and earning 9,380 baht a month. Malnutrition was reported as 8.4 percent were thin, 7.2 percent short and 7.2 percent obese. Based on DSI screening test of the Department of Mental Health, normal child development was reported among 73.1 percent of them. Their delayed domains were personal - social skills, fine motor and language. Factors significantly affecting child development (p value < 0.05) were marital status, family income, financing sufficiency, family relation and interactive toys. Therefore, child development can be strengthened further by relevant policy, and support for screening, and promotion of child development.